Mutual Identity Authentication Based on Dynamic Identity and Hybrid Encryption for UAV–GCS Communications - Lin Lin; Runzong Shangguan; Hongjuan Ge; Yinchuan Liu; Yuefei Zhou; Yanbo Zhou (Drones)
In order to solve the problems of identity solidification, key duration, and lack of anonymity in communications between unmanned aerial vehicles (UAVs) and ground control stations (GCSs), a mutual secure communication scheme named Dynamic Identity and Hybrid Encryption is proposed in this paper. By constructing an identity update mechanism and a lightweight hybrid encryption system, the anonymity and untraceability of the communicating parties can be realized within a resource-limited environment, and threats such as man-in-the-middle (MITM) attacks, identity forgery, and message tampering can be effectively resisted. Dynamic Identity and Hybrid Encryption (DIHE) uses a flexible encryption strategy to balance security and computing cost and satisfies security attributes such as mutual authentication and forward security through formal verification. Our experimental comparison shows that, compared with the traditional scheme, the calculation and communication costs of DIHE are lower, making it especially suitable for the communication environment between UAVs and GCSs with limited computing power, thus providing a feasible solution for secure low-altitude Internet of Things (IoT) communication.